1999
DOI: 10.1093/ndt/14.3.738
|View full text |Cite
|
Sign up to set email alerts
|

Homocyst(e)ine and vascular access complications in haemodialysis patients: insights into a complex metabolic relationship

Abstract: We did not demonstrate a relationship between tHcy and risk of vascular access failure. Patients with the lowest levels of tHcy appeared to be at increased risk of death in this short-term follow-up. The relationship of tHcy to vascular access complications and death in haemodialysis patients appears complex and requires further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
27
1
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 4 publications
7
27
1
1
Order By: Relevance
“…Hyperhomocysteinemia is present in the vast majority of maintenance dialysis patients according to almost all descriptive and prevalent studies (5)(6)(7)(8)(9)(10)(11)(12). In most of such studies, including our current study, Ͼ90% of maintenance dialysis patients have hyperhomocysteinemia, and the mean and median values of tHcy are between 20 and 25 mol/L.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…Hyperhomocysteinemia is present in the vast majority of maintenance dialysis patients according to almost all descriptive and prevalent studies (5)(6)(7)(8)(9)(10)(11)(12). In most of such studies, including our current study, Ͼ90% of maintenance dialysis patients have hyperhomocysteinemia, and the mean and median values of tHcy are between 20 and 25 mol/L.…”
Section: Discussionsupporting
confidence: 49%
“…Almost 72% of the patients were taking daily multivitamin supplementation designed specifically for patients with renal failure, which usually includes 1000 g of folic acid. These pills included nephrovite (209), nephrocaps (10), and other brands (46). Moreover, 86 patients were taking folic acid supplement, 1000 g/d, including 67 who were also taking above-mentioned multivitamins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the eleven cohort studies only two failed to find an increased risk of vascular disease associated with elevated homocysteine levels. One of these studies, by Sirrs et al (1999) in haemodialysis patients, actually observed an inverse relationship between homocysteine levels and mortality, suggesting that lower homocysteine levels were actually associated with an increased risk of death. The follow-up period in this study, however, was very short.…”
Section: Prospective Studiesmentioning
confidence: 99%
“…The development of VAT is characterized by neointimal hyperplasia and luminal stenosis 1) . Increasing evidence suggests that VAT is associated with an increase of systemic inflammation markers, such as C-reactive protein (CRP) 2) and homocysteine [3][4] , in chronic HD patients. Increases of inflammatory markers, such as interleukin-6, were also identified in vascular access stenotic lesions 5) .…”
Section: Introductionmentioning
confidence: 99%